“Their skirts are too short!” and “He’s gay!”. Backlashes on Transnational Popular Culture Consumption in BlackPink and Bright’s Case Studies - Ghaziah Nurika Akhni (Center for Southeast Asian Social Studies (CESASS), 2022)
The internet era has facilitated online streaming and social media platforms to burgeon, causing the flow of transnational pop cultures across regions and also offering diverse consumption of media content from around the globe. In Indonesia, the discussion on pop culture has often been centered on the proliferation of K-Pop's popularity among local audiences. Besides, the Boys Love (BL/Y) series from Thailand has also gained considerable interest in the last couple of years. While the consumption of K-Pop and Thailand's BL series in global mediascape is widely accepted without much controversy, incongruous feedbacks are present among Indonesian audiences, particularly pointing at the clash of ideological perspectives between its Muslim conservatives and the youth. The conservative group considers the media contents